MUSIC THERAPY IN THE LEARNING PROCESS - Ana Rosaura Serrano Buitrago; Fernando Alberto Rengifo Prada (LÍNEA IMAGINARIA, 2025)
Music is a powerful tool to promote learning, as it increases confidence levels, improves self-esteem and security, helps to reduce anxiety levels, improves attention and promotes emotional well-being. An increasing number of educational institutions are committed to applying music therapy in their teaching-learning processes, and the challenge is for teachers to include music in their classes as a means of overcoming learning difficulties and increasing students' confidence in expressing their emotions. The aim of this paper is to describe how music therapy can influence students' learning in the classroom, based on the writings of various authors, using documentary research. It can be concluded that music therapy in the classroom plays a fundamental role and its application allows teachers not only to transmit knowledge, but also to facilitate in their students the expression of what they feel and social development in a harmonious and motivating environment. The implementation of music therapy strategies contributes to a positive and enriching classroom climate for learning.